Impact of cropland use changes based on non-agriculturalization, non-grainization and abandonment on grain potential production in Northeast China - Luoman Pu (Scientific Reports)
Abstract Cropland is the basic resource and condition for human survival. However, since 2000, Northeast China has been faced with severe challenges to grain production caused by non-agriculturalization, non-grainization and cropland abandonment, which in turn pose a potential threat to the long-term food security of the whole region and even China. This paper used GIS spatial analysis and statistical analysis methods to explore the impacts of non-agriculturalization, non-grainization and cropland abandonment on grain potential production (GPP) in Northeast China at a grid scale. From 2000 to 2020, the cropland area of Northeast China increased by about 2.10% (9,275.51 km2), and the gravity center of cropland moved to the northeast with a moving distance of 9.18 km. The total lost GPP in Northeast China was 1,410.16 × 104 tonnes due to the non-agriculturalization, non-grainization and abandonment of cropland. Cropland abandonment was the main type of cropland use change leading to the loss of GPP. The dominant type of cropland use change was different in different provinces (regions), leading to different degrees of GPP loss. Heilongjiang Province and Inner Mongolia were dominated by cropland abandonment. Jilin Province and Liaoning province were mainly non-agriculturalization. At the same time, the conversion of cropland to orchards was more common in southern Liaoning Province. Since 2000, the proportion of sown area for grain crops in Northeast China and other provinces (regions) has increased, resulting in an increase of 1,134.76 × 104 tonnes in GPP, which has made up for the loss of GPP caused by other cropland use changes to a certain extent. In the future, measures should be taken to protect cropland, such as restoring agricultural production on abandoned cropland as soon as possible, strengthening the input and policy support of modern agricultural production factors in main grain producing areas, constructing the elastic mechanism of grain production-farmland fallow conversion, improving the intensive utilization rate of urban and rural land, perfecting the balance system of cultivated land occupation and compensation, and perfecting the land circulation mechanism.